Exploring the nature of interaction between shiga toxin producing Escherichia coli (STEC) and free-living amoeba - Acanthamoeba sp - Montalbano Di Filippo, Margherita; Boni, Arianna; Chiani, Paola; Marra, Manuela; Carollo, Maria; Cristofari, Lucrezia; Minelli, Fabio; Knijn, Arnold; Morabito, Stefano (Frontiers in Cellular and Infection Microbiology, 2022)
Free-living amoebae (FLA) are widely distributed protozoa in nature, known to cause severe eye infections and central nervous system disorders. There is growing attention to the potential role that these protozoa could act as reservoirs of pathogenic bacteria and, consequently, to the possibility that, the persistence and spread of the latter may be facilitated, by exploiting internalization into amoebae. Shiga toxin-producing strains of Escherichia coli (STEC) are zoonotic agents capable of causing serious diseases, such as hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS). Cattle represent the main natural reservoir of STEC, which are frequently found also in other domestic and wild ruminants, often without causing any evident symptoms of disease. The aspects related to the ecology of STEC strains in animal reservoirs and the environment are poorly known, including the persistence of these microorganisms within niches unfavorable to survival, such as soils or waters. In this study we investigated the interaction between STEC strains of serotype O157: H7 with different virulence gene profiles, and a genus of a wild free-living amoeba, Acanthamoeba sp. Our results confirm the ability of STEC strains to survive up to 20 days within a wild Acanthamoeba sp., in a quiescent state persisting in a non-cultivable form, until they reactivate following some stimulus of an unknown nature. Furthermore, our findings show that during their internalization, the E. coli O157 kept the set of the main virulence genes intact, preserving their pathogenetic potential. These observations suggest that the internalization in free-living amoebae may represent a means for STEC to resist in environments with non-permissive growth conditions. Moreover, by staying within the protozoa, STEC could escape their detection in the vehicles of infections and resist to the treatments used for the disinfection of the livestock environment